'From a hurt sense of honor': violence work and the limits of soldierly obedience on a scientific expedition in German East Africa, 1896–1897. (3rd July 2018) - Moyd, Michelle
ABSTRACT: In 1896, a German army lieutenant led a militarized geographic expedition across German East Africa. Testimonies generated during an inquiry into the officer's various abuses during the expedition illustrate how tensions between Werther and his soldiers shaped their uses of violence as they marched from the coast to the interior in search of gold and other possibilities for colonial economic extraction. The testimonies also offer rare insight into the military column's internal dynamics, where race, rank, and labor hierarchies disrupted military order, exacerbating violence perpetrated against African peoples along the column's path.